N6-methyladenine is an epigenetic marker of mammalian early life stress. Issue 1 (December 2017) - Kigar, Stacey; Chang, Liza; Guerrero, Candace; Sehring, Jacqueline; Cuarenta, Amelia; Parker, Laurie; Bakshi, Vaishali; Auger, Anthony
Abstract Recent evidence described 6-methyladenine (6 mA) as a novel epigenetic regulator in a variety of multicellular species, including rodents; however, its capacity to influence gene expression in the mammalian brain remains unknown. We examined if 6 mA is present and regulated by early life stress associated with predator odor exposure (POE) within the developing rat amygdala. Our results provide evidence that 6 mA is present in the mammalian brain, is altered within theHtr2a gene promoter by early life stress and biological sex, and increased 6 mA is associated with gene repression. These data suggest that methylation of adenosine within mammalian DNA may be used as an additional epigenetic biomarker for investigating the development of stress-induced neuropathology.